Genome-wide association study identifies a novel locus associated with psychological distress in the Japanese population - Koshimizu, Hisatsugu (Transl Psychiatry, 2019)
Major depressive disorder (MDD) is a common and disabling psychiatric disorder. A recent mega analysis of genome-wide association studies (GWASs) identified 44 loci associated with MDD, though most of the genetic etiologies of the MDD/psychological distress remain unclear. To further understand the genetic basis of MDD/psychological distress, we conducted a GWAS in East Asia with more than 10,000 participants of Japanese ancestry who had enrolled in a direct-to-consumer genetic test. After quality control on the genotype data, 10,330 subjects with a total of 8,567,708 imputed SNPs were eligible for the analysis. The participants completed a self-administered questionnaire on their past medical history and health conditions that included the 6-item Kessler screening scale (K6 scale) for psychological distress (cut-off point of 5) and past medical history of MDD, resulting in 3981 subjects assigned to “psychologically distressed group” [cases], and the remaining 6349 subjects were assigned to the “non-psychologically distressed group” [controls]. In this GWAS, we found an association with genome-wide significance at rs6073833 (P = 7.60 × 10(−9)) in 20q13.12. This is, to the best of our knowledge, the first large-scale GWAS for psychological distress using data from direct-to-consumer (DTC) genetic tests in a population of non-European-ancestry, and the present study thus detected a novel locus significantly associated with psychological distress in the Japanese population.